Cyanomargarita gen. nov. (Nostocales, Cyanobacteria): convergent evolution resulting in a cryptic genus - Shalygin, S.; Shalygina, R.; Johansen, J. R.; Pietrasiak, N.; Gómez, E. B.; Bohunická, M.; Mareš, J. (Jan); Sheil, C.A. (Journal of Phycology, 2017)
Two populations of Rivularia-like cyanobacteria were isolated from ecologically distinct and biogeographically distant sites. One population was from an unpolluted stream in the Kola Peninsula of Russia, whereas the other was from a wet wall in the Grand Staircase-Escalante National Monument, a desert park-land in Utah. Though both were virtually indistinguishable from Rivularia in field and cultured material, they were both phylogenetically distant from Rivularia and the Rivulariaceae based on both 16S rRNA and rbcLX phylogenies. We here name the new cryptic genus Cyanomargarita gen. nov., with type species C. melechinii sp. nov., and additional species C. calcarea sp. nov. We also name a new family for these taxa, the Cyanomargaritaceae.